The composer is dead - Snicket, Lemony; Ellis, Carson, 1975-; Stookey, Nathaniel (New York : HarperCollins, 2009)
An inspector seeks to solve a murder mystery at the symphony by questioning each of the musical instruments.
"There's dreadful news from the symphony hall, the composer is dead! If you have ever heard an orchestra play, then you know that musicians are most certainly guilty of something. Where exactly were the violins on the night in question? Did anyone see the harp? Is the trumpet protesting a bit too boisterously? In this perplexing murder mystery, everyone seems to have a motive, everyone has an alibi, and nearly everyone is a musical instrument. But the composer is still dead. Perhaps you can solve the crime yourself. Join the Inspector as he interrogates all the unusual suspects. Then listen to the accompanying audio recording featuring Lemony Snicket and the music of Nathaniel Stookey performed by the San Francisco Symphony. Hear for yourself exactly what took place on that fateful, well-orchestrated evening"--Container.
CD tracks 10-18: instrumental only.
Narrated by Lemony Snicket.
Performed by the San Francisco Symphony.
Ages 5 up.
Keywords: Musical instruments -- Fiction; Orchestra -- Fiction; Murder -- Fiction; Criminal investigation -- Fiction